2020
DOI: 10.5194/acp-20-14801-2020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 3D electric field on saltation during dust storms: an observational and numerical study

Abstract: Abstract. Particle triboelectric charging, being ubiquitous in nature and industry, potentially plays a key role in dust events, including the lifting and transport of sand and dust particles. However, the properties of the electric field (E field) and its influences on saltation during dust storms remain obscure as the high complexity of dust storms and the existing numerical studies are mainly limited to the 1D E field. Here, we quantify the effects of the real 3D E field on saltation during dust storms thro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 71 publications
(184 reference statements)
0
5
0
Order By: Relevance
“…Therefore, the electrical properties of suspended dust particles in dust storms are currently unclear, and the particles' charge-to-mass ratio is usually assumed to be a constant of ∼ ± 60 µC kg −1 in many numerical models (e.g. Schmidt et al, 1998;Zhang & Zhou, 2020a;Zheng et al, 2003); this magnitude is consistent with the measurements of (Schmidt et al, 1998). Although Williams, Nathou, Hicks, Pontikis, and Bartholomew (2009) inferred that the charge structure of dust storms may be unipolar or bipolar (if particle charging occurs primarily at the ground or in midair, respectively), they neglected the effects of turbulence, which plays an important role in particle charging (e.g.…”
Section: Electric Field Measurements In Dust Stormsmentioning
confidence: 99%
“…Therefore, the electrical properties of suspended dust particles in dust storms are currently unclear, and the particles' charge-to-mass ratio is usually assumed to be a constant of ∼ ± 60 µC kg −1 in many numerical models (e.g. Schmidt et al, 1998;Zhang & Zhou, 2020a;Zheng et al, 2003); this magnitude is consistent with the measurements of (Schmidt et al, 1998). Although Williams, Nathou, Hicks, Pontikis, and Bartholomew (2009) inferred that the charge structure of dust storms may be unipolar or bipolar (if particle charging occurs primarily at the ground or in midair, respectively), they neglected the effects of turbulence, which plays an important role in particle charging (e.g.…”
Section: Electric Field Measurements In Dust Stormsmentioning
confidence: 99%
“…There are additional interesting features to note. While it has been known that electrical fields are present during dust emission and play a role in the amount of dust lifted (Esposito et al, 2016;Kok and Renno, 2008;Zhang and Zhou, 2020), non-background electrical fields are also found in dust clouds at significant distance from the sources such as dust reaching Greece and the UK (Daskalopoulou et al, 2021;Harrison et al, 2018). These studies suggested triboelectrification (i.e., friction between particles) as mechanism for generation of an electric field within the cloud during transit.…”
Section: Alignment Of Particle As a Source Of Circular Polarizationmentioning
confidence: 99%
“…However, as the main objective of this study is to eliminate the dependence of the initial motion parameters on the empirical or semi-empirical results obtained by experiments and theories, we ignore this process as in most of the previous studies (Anderson & Haff, 1991;Kok & Renno, 2009). In addition, considering the relatively small wind speed and uniform sand used in our wind tunnel scale simulation, the effects of electrostatic forces on particle motion are neglected (Kok & Renno, 2008;Zheng et al, 2003;Zhang & Zhou, 2020). The motion equation of a point-particle model mainly considers the action of drag and gravitational forces, which can be described as (Vinkovic et al, 2006;Wang & Squires, 1996;Yamamoto et al, 2001):…”
Section: Particle Solvermentioning
confidence: 99%